Implementasi Senam Aerobic Low Impact untuk Mengurangi Nyeri Pinggang pada Lansia - Lintang Wening Pembayun; Rifatul Maulidina; Gabriella Jesicca Eriesti; Nita Amalia Nur Azizah; Risma Aliviani Putri; Isfaizah (Universitas Ngudi Waluyo, 2025)
Older adults often experience a decline in physical function that can lead to musculoskeletal problems, particularly low back pain. This community service article aims to describe the implementation of an aerobic low-impact exercise program to reduce low back pain and to improve the knowledge and skills of Posyandu Lansia managers in Ampelgading Hamlet, Kenteng Village. The program community service involved elderly participants aged 50–80 years and Posyandu managers. Activities included health education, demonstration and practice of aerobic low-impact exercises, and the use of an instructional exercise video. Evaluation was conducted using pre- and post-tests to assess managers’ knowledge and skills, as well as questionnaires to observe changes in low back pain complaints among the elderly. The results showed an improvement in the knowledge and skills of Posyandu managers after the training. In addition, elderly participants reported a decrease in low back pain complaints after participating in the exercise program. In conclusion, aerobic low-impact exercise supported by education and video guidance is a simple and effective approach to support community-based elderly health programs and improve physical comfort among older adults. Abstrak Lansia sering mengalami penurunan fungsi fisik yang dapat menyebabkan masalah muskuloskeletal, khususnya nyeri punggung bawah. Artikel pelayanan masyarakat ini bertujuan untuk menggambarkan implementasi program latihan aerobik berdampak rendah untuk mengurangi nyeri punggung bawah dan meningkatkan pengetahuan serta keterampilan para pengelola Posyandu Lansia di Dusun Ampelgading, Desa Kenteng. Program ini melibatkan peserta lansia berusia 50–80 tahun dan para pengelola Posyandu. Kegiatan meliputi pendidikan kesehatan, demonstrasi dan praktik latihan aerobik berdampak rendah, serta penggunaan video instruksional latihan. Evaluasi dilakukan menggunakan pretest dan posttest untuk menilai pengetahuan dan keterampilan para pengelola, serta kuesioner untuk mengamati perubahan keluhan nyeri punggung bawah di kalangan lansia. Hasil menunjukkan para lansia dapat mempraktekkan senam low impact setelah pelatihan. Selain itu, peserta lansia melaporkan penurunan keluhan nyeri punggung bawah setelah mengikuti program latihan. Kesimpulannya, olahraga aerobik berdampak rendah yang didukung oleh edukasi dan panduan video merupakan pendekatan sederhana dan efektif untuk mendukung program kesehatan lansia berbasis komunitas dan meningkatkan kenyamanan fisik di kalangan lansia.